O influxo da política sobre a concretização constitucional - Silva, Marília Ferreira da (2014)
Given the problems that plague modern version of State Constitutional Law, therefore, this study seeks alternatives that promote the balance of its parts, focusing on the pursuit of social welfare. It is known that the legalistic alternative collapsed on its shortcomings, giving rise optimizing alternative. The excesses of absolutism coming from the positive law began to be weighted by the "malleability" of the legal principiologismo. However, taking the principles assumed the function of the exhaust system valve, eventually belittle the essentiality of legal rules, ordinarizando its application in a "capricious decisionismo" sometimes uncompromising with rational argument and the constitutional system. This expedient is the symbolic vector hypertrophy legislating activity, due to the mismatch between feasible policy and law that breaks (u) with the "structural coupling" and compels the judiciary to meet political and legal needs without worrying about the social and normative effects coming, "an artificial coupling" and is a typical case of symbolic legislation, the legislature discharges of public pressure, confirming social values and postpones the solution of socio-politico-legal issues, and the jurist, in turn, intensifies and (re) affirms the ideological role of constitutional norms, shielding the system and creating the image of a state that responds to the demands imposed normatively while that immunizes itself, manipulating and deceiving the masses. However, the search for measures that will promote the densification of the constitutional embodiment, it is concluded that inobstante necessary to give more objective rationality and the hermeneutics of constitutional principiologia, Economic Analysis of Law parameters does not meet the satisfaction this role, since open space for economic judgments of legal demands resonate in immobilization of law such that, causing reverse effect, greatly affront the realization of fundamental rights that dignify, since human life directly dependent on the state budget availability. This time, considering that this is the normative core limiting the role of interpreter, administrator and legislator, any compromise of his achievement should be dismissed immediately. What is certain is that the law of postmodernity requires expansion and fortification of citizenship, absolute realization of fundamental rights and unanswerable application of constitutional principles by rational argumentative procedure of promoting unrestricted socio-legal inclusion, at which, in a society and conscious and polished, a natural shield against interference politicals that degrade the constitutional environment, and thus a consistent constitutionally appropriate legal and socially embodiment shall be taken.